2020
DOI: 10.1155/2020/2196418
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Urbanization and Socioeconomic Factors on the Distribution of Cutaneous Leishmaniasis in the Center of Morocco

Abstract: Background. Parasitic diseases, in particular leishmaniasis, are still a public health problem in several countries and in Morocco. Methods. The data used are those of epidemiological surveillance collected in the registers of the prefectural epidemiology cell (PEC); however, the socioeconomic data were obtained from the High Commissioner for Planning. The Pearson correlation test was used to determine the correlation between the different variables. Results. In total, 70 cases were recorded by the prefectural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 14 publications
2
20
1
Order By: Relevance
“…In this retrospective study, we determined that the increase in cases of leishmaniasis among the Andean rural population was related to poverty and extreme poverty rates, showing that the highest incidence rate was 0.93×1000 inhabitants (with an increase of 21% in cases between 2015 and 2020). This increase in cases may be due to poor control and surveillance of the disease, as has been seen in other low-settings countries [13]. Previous studies in South American countries [14][15][16] have also shown a link between leishmaniasis and poverty, which is consistent with our findings in the weakest districts of Celendín.…”
Section: Discussionsupporting
confidence: 91%
“…In this retrospective study, we determined that the increase in cases of leishmaniasis among the Andean rural population was related to poverty and extreme poverty rates, showing that the highest incidence rate was 0.93×1000 inhabitants (with an increase of 21% in cases between 2015 and 2020). This increase in cases may be due to poor control and surveillance of the disease, as has been seen in other low-settings countries [13]. Previous studies in South American countries [14][15][16] have also shown a link between leishmaniasis and poverty, which is consistent with our findings in the weakest districts of Celendín.…”
Section: Discussionsupporting
confidence: 91%
“…As in most countries around the Mediterranean, leishmaniasis in Morocco constitutes a serious public health problem [ 12 ] because of its clinical and epidemiological diversity [ 13 ]. Leishmaniasis in these different forms are endemic in many areas, each with its own vectors and reservoirs [ 14 , 15 ]; the number of cases reported in 2015 by the Epidemiology Department of the Moroccan Ministry of Public Health is 2 900 cases of leishmaniasis.…”
Section: Introductionmentioning
confidence: 99%
“…At the national and especially regional level, our result also substantiates that of Hajar El Omari. At the level of Meknes, it has been shown that the poverty factor does not influence the distribution of the number of CL cases [35]. Other studies have shown the opposite.…”
Section: Discussionmentioning
confidence: 93%